题目内容
(1)计算:2
×
×
(2)化简:(-2x
y-
)(3x-
y
)(-4x
y
).
3 |
3 | 1.5 |
6 | 12 |
(2)化简:(-2x
1 |
4 |
1 |
3 |
1 |
2 |
2 |
3 |
1 |
4 |
2 |
3 |
(1)2
×
×
=2×3
×(
)
×12
=2×3
×3
×3
×2-
×2
=2×3
+
+
×20
=2×3=6;
(2)(-2x
y-
)(3x-
y
)(-4x
y
)
=(-2)×3×(-4)x
-
+
y-
+
+
=24y.
3 |
3 | 1.5 |
6 | 12 |
=2×3
1 |
2 |
3 |
2 |
1 |
3 |
1 |
6 |
=2×3
1 |
2 |
1 |
3 |
1 |
6 |
1 |
3 |
1 |
3 |
=2×3
1 |
2 |
1 |
3 |
1 |
6 |
=2×3=6;
(2)(-2x
1 |
4 |
1 |
3 |
1 |
2 |
2 |
3 |
1 |
4 |
2 |
3 |
=(-2)×3×(-4)x
1 |
4 |
1 |
2 |
1 |
4 |
1 |
3 |
2 |
3 |
2 |
3 |
=24y.
![](http://thumb.zyjl.cn/images/loading.gif)
练习册系列答案
相关题目